Enhancement of the corrosion resistance for stainless steel 316 by applying laser shock peening - Jasim Sarah A.; Ayesh Ammar; Kadhim A.; Abdullah Oday I. (Polish Journal of Chemical Technology, 2024)
This research paper focuses on enhancing the surface characteristics of the 316 stainless steel (SS316) alloy, including roughness, microhardness, and corrosion resistance. Where the application of ND-YAG laser technology, a highly relevant and timely area, was investigated deeply. The Q-switching Nd: YAG Laser was used with varying laser energy levels within the context of the laser shock peening (LSP) technique. The corrosion resistance of the 316 ss alloy is evaluated in a corrosive environment of 500 mL of saliva (with a pH of 5.6) through electrochemical corrosion testing. Corrosion rate was determined based on the analysis of polarization curves. The outcomes of this research reveal that as the laser energy was increased, there was a noticeable enhancement in the mechanical properties of the 316 ss alloy’s surface. Importantly, the corrosion rate experiences a significant reduction, decreasing from 4.94 mm/yr to 3.59 mm/yr following laser shock peening (LSP) application.